THE IMPORTANCE OF PLANNING AND MANAGING STORAGE IN PEANUT HARVESTING: A CASE STUDY CONDUCTED IN A COOPERATIVE - da Silva Inácio, Lucas; Vitória Braulino Ferreira, Kemily; Aparecido Marinho, Clésio (Revista Gênero e Interdisciplinaridade, 2026)
This study analyzed how the lack of accurate estimates and adequate planning can compromise the efficiency of peanut storage management in an agricultural cooperative located in the Sertãozinho region of São Paulo. Using a qualitative, exploratory case study method, the research involved document analysis, semi-structured interviews, and direct observation of operational practices. The results showed that, although the cooperative has organized and standardized processes, it still faces challenges related to technological integration and production predictability. Advance planning and control of environmental variables, such as humidity and temperature, proved to be fundamental to ensuring grain quality and reducing losses. In addition, the adoption of appropriate storage methods—in bags, bulk, or sacks—contributes to product conservation and safety. It was found that planning based on historical indicators and volume safety margins allows for a better balance between grain inflow and outflow, ensuring logistical efficiency. It is concluded that investment in infrastructure, automation, and forecasting technologies is essential to improve storage management, promote sustainability, and increase the competitiveness of the peanut production chain.